309. ASSESSMENT AND MANAGEMENT AFTER CORROSIVE INGESTION: WHEN IS SPECIALIST CENTRE REFERRAL NEEDED? A 10-YEAR UK EXPERIENCE. (24th September 2022) - Di Maggio, Francesco; Vergani, Vittoria; Tomasi, Ivan; Zhang, Chuan; Gossage, James; Botha, Abrie; Baker, Cara
Abstract: Corrosive ingestion injuries are rare but clinically significant events, potentially associated with high morbidity and mortality. Low case-volumes limits guideline development. We report the largest UK cohort of patients admitted consecutively to a UGI tertiary referral centre after caustic ingestion, over a period of 10 years. Clinical presentation, diagnostics and treatment modalities as well as short and long-term outcomes were analysed, to produce evidence and the recommendation for centralization of management only of severe injuries. All adults treated following corrosive ingestion between 2010 and 2020 were included. Eighty-one patients were included, with an average follow-up of 5 years. Blood results, imaging and endoscopic findings were reviewed. Patients were stratified based on endoscopic findings. Emergency and delayed management was analysed along with short and long-term outcomes. Predictive value of early outcome indicators was investigated. Patients with injuries ≤ Zargar 2A had long-term outcomes similar to the ones with negative endoscopic findings. All fifteen patients suffering injuries Zargar ≥2B required ITU and four died (26.6%). All deaths occurred within 50 days of ingestion, had Zargar grade ≥ 3 and airway involvement. Five patients (33%) required emergency operations, two of which died. All Zargar ≥2B injury survivors (n = 11) developed strictures and/or tracheo-esophageal fistulae (18%), required multiple admissions and prolonged nutritional support; five required delayed resections. Zargar grade ≥ 2B, airway damage, and increased CRP on admission correlated with unfavourable outcomes. Corrosive ingestion injuries up to Zargar 2A do not cause long-term sequelae and can be managed locally. Injuries. > 2B bear high mortality and will cause sequelae. Early identification of severe injuries and transfer to specialist centres with multidisciplinary ITU, OG, thoracic and ENT expertise is recommended.